A political economy model of monetary policy: decentralized decision making and competition for seigniorage - Hillbrecht, Ronald (Brazilian Journal of Political Economy, 1999)
A political economy model is developed to provide a rationale of monetary policy in high inflation regimes, such as the Brazilian experience until the advent of the Plano Real. Decision making of monetary policy is assumed to be decentralized, where several decision- -makers competitively determine the quantity of money. It is shown that equilibrium inflation is higher than under the alternative monetary regime where decision making is centralized at the Central Bank. An important additional feature of this political economy model is that it does not rely on time-inconsistency to generate high and sub-optimal inflation. JEL Classification: E52; G21; H21.